2008
DOI: 10.1186/cc6890
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial treatment for ventilator-associated tracheobronchitis: a randomized controlled multicenter study

Abstract: Introduction Ventilator-associated tracheobronchitis (VAT) is associated with increased duration of mechanical ventilation. We hypothesized that, in patients with VAT, antibiotic treatment would be associated with reduced duration of mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
153
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 46 publications
3
153
0
7
Order By: Relevance
“…In the present study, systemic antibiotics were frequently administered to VAT patients under the guidance of physicians, in short courses followed by deescalation. Antibiotic treatment in the present study witnessed lower rates of clinical signs and symptoms, faster weaning followed by extubation, Nseir et al, (2008) conducted a randomized, controlled, multicentric study on antimicrobial treatment for ventilator associated tracheobronchitis. And the study suggested that patients with VAT, compared with matched control subjects, had significantly lower median duration of mechanical ventilation and longer duration of ICU stay in patient treated with appropriate antibiotics, but antibiotic therapy did not appear to protect against VAP.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the present study, systemic antibiotics were frequently administered to VAT patients under the guidance of physicians, in short courses followed by deescalation. Antibiotic treatment in the present study witnessed lower rates of clinical signs and symptoms, faster weaning followed by extubation, Nseir et al, (2008) conducted a randomized, controlled, multicentric study on antimicrobial treatment for ventilator associated tracheobronchitis. And the study suggested that patients with VAT, compared with matched control subjects, had significantly lower median duration of mechanical ventilation and longer duration of ICU stay in patient treated with appropriate antibiotics, but antibiotic therapy did not appear to protect against VAP.…”
Section: Resultsmentioning
confidence: 89%
“…Most of the Acinetobacter baumannii isolates were recovered during 12-13 days of mechanical ventilation. Increasing numbers of lower respiratory tract pathogens over time following intubation are likely to be a sign of increased bacterial virulence, greater inflammation and risk of progression from colonization to VAT (Nseir et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…4 Some reports suggest that patients with VAT also have increased length of ICU stay and a prolonged need for mechanical ventilation. 5,6 To gain a better understanding of the molecular mechanisms that underlie the lung phenotypes in VAT vs VAP, we sought to identify and compare their gene expression ''signatures'' using genome-wide oligonucleotide microarrays. We hypothesized that VAP/VAT would exhibit different gene expression signatures which could help to distinguish between the two conditions and would also shed light on their pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies (3/4 studies) showed that antimicrobial treatment did not decrease the duration of mechanical ventilation or length of stay in an ICU, although two randomized controlled trials showed that the frequency of progression to VAP was lower in patients receiving antimicrobial therapy for VAT (251). Nseir and colleagues completed several well-designed trials with patients with VAT indicating that systemic antibiotic therapy improves outcomes and re-duces the progression to VAP, although these studies did not examine inhaled therapies (252). Despite the limited number of reported studies evaluating the use of inhaled antibiotics for VAT, given the localized pathophysiology, it is sensible to conclude that inhaled agents may be equally as effective as systemic agents with regard to clinical and microbiological outcomes.…”
Section: Ventilator-associated Tracheobronchitismentioning
confidence: 99%